Common Cast ComplicationsMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's Method - Jessica A. McGraw-Heinrich, MD; Jon C. Wall, MD; Scott B. Rosenfeld, MD (Journal of the Pediatric Orthopaedic Society of North America, 2025)
Complications can arise from the application, wear, and removal of casts and splints. This text reviews common complications, risk factors, and prevention strategies while exploring the medical-legal implications of these complications. Being aware of common pitfalls can help reduce risk and promote optimal patient outcomes. Key Concepts: (1) Proper and judicious casting and splinting techniques are critical to prevent complications. (2) Thermal injuries can occur due to excessive curing heat and cast saw burns. (3) Poor cast molding can lead to skin sores and loss of fracture reduction. (4) Patients should be comfortable in their cast, and uncontrolled pain warrants investigation.